2022
DOI: 10.1044/2022_persp-21-00315
|View full text |Cite
|
Sign up to set email alerts
|

Validating Spectral Moment Analysis as a Quantitative Measure of Speech Distortions in Speakers With Class III Malocclusions

Abstract: Purpose: This study examined the relationship between judged speech sound distortions and spectral moment metrics in speakers with Class III malocclusion. Method: A quantitative online survey was distributed to 30 speech specialists (clinicians and/or students) and 100 lay listeners to judge the clarity of the sounds /s/, /ʃ/, /t/, and /k/ using a visual analog scale (VAS) from recordings of 11 Class III (underbite) dentofacial disharmony (DFD) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…To evaluate the relevance of these acoustic measures for perceptual judgments of speech distortion, we used a set of perceptual judgments collected by Jhingree et al (2022) , which included the consonants /s ʃ t k/ for 25 of the participants whose acoustic data are included in this study (10 Class III closed bite, four Class III AOB, one Class I AOB, and eight Class I controls). The listeners were 30 speech specialists who were asked to rate the level of perceived distortion in the initial consonant of words presented in isolation on a visual analog scale ranging from 0 (completely clear) to 100 (severely distorted).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the relevance of these acoustic measures for perceptual judgments of speech distortion, we used a set of perceptual judgments collected by Jhingree et al (2022) , which included the consonants /s ʃ t k/ for 25 of the participants whose acoustic data are included in this study (10 Class III closed bite, four Class III AOB, one Class I AOB, and eight Class I controls). The listeners were 30 speech specialists who were asked to rate the level of perceived distortion in the initial consonant of words presented in isolation on a visual analog scale ranging from 0 (completely clear) to 100 (severely distorted).…”
Section: Methodsmentioning
confidence: 99%
“…Certain consonants are more likely to be affected by different DFDs. Bilabial consonants and sibilants were found to be the most challenging for Class II patients to produce, while Class III patients showed the most difficulty in producing stop and affricate consonants; AOB patients present with the highest prevalence of auditory distortion of fricative consonants ( Jacox et al, 2022 ; Jhingree et al, 2022 ; Keyser et al, 2022 ; Lathrop-Marshall et al, 2022 ; Oliver et al, 2023 ). Grudziąż-Sękowska et al (2018) and Assaf et al (2021) found an association between malocclusion and speech distortion in children.…”
mentioning
confidence: 96%